Effect of Ageing on Semantic and Phonetic Information Processing. - Kooknoor, Vishal; Shetty, Hemanth Narayana (Auditory & Vestibular Research (2423-480X), 2025)
Background and Aim: To understand the difficulties of elderly in natural listening situations, the present study assessed the ability of participants to extract phonetic information and semantic information in noise. The main objective was to evaluate the relationship between age and performance in Semantic Information Processing (SIP) and Phonetic Information Processing (PIP) tasks. Methods: Fifty-three normal hearing participants aged 40 to 65 years were categorized into five age groups. Participants underwent information processing assessments using standardized semantic and phonetic questions from Kannada stories under Signal-to-Noise Ratios (SNR) i.e., quiet, 0 dB SNR, and -4 dB SNR conditions. Results: Younger participants outperformed older participants in both SIP and PIP tasks. Performance was optimal in quiet conditions, followed by 0 dB and -4 dB SNR. Except at -4 dB, PIP scores exceeded SIP scores. A significant differences was observed between the groups 1-4 and group 5 at 0 dB SNR in PIP condition only. A moderate negative correlations indicated that performance in both SIP and PIP declined with age, with linear regression revealing reductions of 0.216 and 0.210 each year in SIP and PIP respectively. Conclusion: Age-related declines in PIP were noted at one SNR, while SIP remained stable, aligning with the Transmission Deficit Hypothesis (TDH). Nonetheless, regression analyses indicated a general decline in both SIP and PIP with age, supporting the Inhibitory Deficit Hypothesis (IDH).